The political imaginaries and social lives of political prisoners in post-2000 Zimbabwe - Alexander, J (Routledge, 2010)
This article situates the experiences of political prisoners in post-2000 Zimbabwe in a historical sequence of imprisonment. It uses prisoners' narratives to examine the shifting political ideas and social and material practices that shaped opposition politics. I explore the centrality of ideas about the rule of law, the practices and beliefs through which social and political connection and community were built within and beyond the prison walls, and the terrible and often enduring costs of imprisonment. Although prisoners' narratives were often marked by tales of irredeemable loss, they also underlined the importance to opposition political imaginaries of bonds built across the barriers of race, class and respectability and claims to a rights-bearing citizenship.